(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
The atypical antipsychotic drugs used in recent times for the treatment of chronic or acute psychotic (CNS) disorders, are found to cause Extrapyramidal side effects (EPS). Earlier studies have revealed that an enhanced oxidative stress accompanied with high glutamate transmission lead to extrapyramidal symptoms, thus limiting the use of established antipsychotic drugs. Therefore the current study investigates the effects of 6-fluoro-3-(piperidin-4-yl) benzo[d]isoxazole derivatives designated as S1, S2, S3, S4 as potent antipsychotics and to prove their efficacy in producing menial Extrapyramidal symptoms, by conducting biochemical, neurochemical and behavioural analysis. The behavioural studies on mice showed that chronic administration of standard antipsychotic drugs haloperidol (1 mg/kg i.p) and resperidone (1 mg/kg i.p) to animals have remarkably increased the vacuous chewing movements (VCM`s), VCM`s was noticeably inhibited in test compounds S2 and S3 (1 mg/kg i.p). Neurochemical analysis showed an increase in the concentrations of GABA, dopamine, and norepinephrine in the mice treated with synthesized molecules (S1-S4) compared to standard drugs. Alterations in the enzyme/protein levels of GSH, SOD, catalase and lipid peroxidation have further substantiated the role of free radicals as the underlying cause of EPS. Altogether it can be concluded that the study of synthetic molecules may yield a promising antipsychotic drug which can minimise EPS.